Sharing economy in hospitality and tourism: a review and the future pathways - Kuhzady, Salar; Olya, Hossein; Farmaki, Anna; Ertaş, Çağdaş (ROUTLEDGE, 2021)
his paper aims to provide a systematic review of the academic literature on the sharing economy (SE) phenomenon within hospitality and tourism and identify knowledge gaps that may present opportunities for further research. Using Scopus and WOS, 486 articles published from 2010 to 2019 were identified, out of which three themes emerge as predominant: 1) drivers to participate in the sharing economy, 2) the sharing economy as a disruptive business model and 3) sharing economy impacts and corresponding regulatory issues. This review paper also reveals that the area of foci of extant literature is hospitality and, in particular the accommodation sector, with most studies drawing insights from the Airbnb context. Contrary to previous review papers on the sharing economy, the systematic review undertaken in this paper presents a holistic attempt to understand the SE phenomenon by exploring a wide range of dimensions related to the topic from multiple sources. Overall, the paper makes a theoretical contribution by providing directions for further research. In addition, it summarizes the key suggestions offered by pertinent studies; thus, offering significant practical insights to practitioners and policymakers.
Keywords: Accommodation; Airbnb; Hospitality; Sharing economy; Systematic review